2008
DOI: 10.1590/s0100-06832008000400027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilizer-N application and seed coating with rhizobial inoculants on soybean yield in eastern Paraguay

Abstract: SUMMARYNitrogen removal in soybean grains at harvest may exceed biological N 2 fixation, particularly if grain yields are as high as typically achieved on "Terra Rossa" soils of Eastern Paraguay. Applying N fertilizer or coating seeds with rhizobial inoculants that enhance nodulation may represent a way of balancing the N budget. However, the effects of such treatments appear to be highly sitespecific. The objective of this study was to examine the effects of N application (N) and rhizobial inoculation (I) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…The reasons for increase in plant height under inoculation and N fertilizer could be due to the increased vegetative growth with applied N and nitrogen fixation. This result is in line with the report of Kubota et al (2008) who stated that plant height of soybean was increase with N in the presence of Rhizobium inoculants. Other authors also reported similar results from researches conducted on chickpea and faba bean, El-Wakeil and El-Sabai (2007) indicating that Rhizobium inoculation significantly increased plant height.…”
Section: Plant Heightsupporting
confidence: 93%
“…The reasons for increase in plant height under inoculation and N fertilizer could be due to the increased vegetative growth with applied N and nitrogen fixation. This result is in line with the report of Kubota et al (2008) who stated that plant height of soybean was increase with N in the presence of Rhizobium inoculants. Other authors also reported similar results from researches conducted on chickpea and faba bean, El-Wakeil and El-Sabai (2007) indicating that Rhizobium inoculation significantly increased plant height.…”
Section: Plant Heightsupporting
confidence: 93%
“…Average over two N levels, increase in plant height, SDW, root length and RDW due to combine application of N with RI was 8, 7, 13 and 3% compared to their respective control. Kubota et al (2008) and Diep et al (2002) obtained increased growth of soybean fertilized with N in the presence of RI. Benefits of inoculation and N application are generally thought to be higher if N is a limiting factor, or deficient in soil (Peoples and Craswell, 1992) or because of large N demand of high yielding cultivars (Dashti et al, 1998).…”
Section: Morphological Characteristicsmentioning
confidence: 93%
“…Benefits of microbial seed coating on crop yield can be of short-term or null according to the growing conditions (Kubota et al, 2008). In fact, not all published research shows positive effects on plant performance of PBM inoculation via seed coating.…”
Section: Seed Coating With Beneficial Microbesmentioning
confidence: 99%